Social character in a Mexican village - Fromm, Erich, 1900-1980; Maccoby, Michael, 1933- (Routledge, Taylor & Francis Group, 2017)
"After the completion of the revolution in 1920, Mexico quickly became an increasingly industrialized country. The vast changes that occurred in the first fifty years after the revolution inspired Erich Fromm and Michael Maccoby to find out how the Mexican people were adapting. The result, Social Character in a Mexican Village, provides a new approach to the analysis of social phenomena. The authors applied Fromm's theories of psychoanalysis to the study of groups. They devised an ingenious method of questionnaires, which, combined with direct observation, clearly revealed the psychic forces that motivated the peasant population. In his new introduction, Michael Maccoby thoroughly explains the basis of the study, how it originated, and how it was carried out. He goes on to delineate the results and determine their impact on the present day. Social Character in a Mexican Village throws new light on one of the world's most pressing problems, the impact of the industrialized world on the traditional character of the peasant. This ground-breaking work will be invaluable to the work of sociologists, anthropologists, and psychoanalysts."--Provided by publisher